2014
DOI: 10.1186/s12951-014-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of antimicrobial biomaterials produced from chitin-nanofiber sheet/silver nanoparticle composites

Abstract: BackgroundChitin nanofibers sheets (CNFSs) with nanoscale fiber-like surface structures are nontoxic and biodegradable biomaterials with large surface-to-mass ratio. CNFSs are widely applied as biomedical materials such as a functional wound dressing. This study aimed to develop antimicrobial biomaterials made up of CNFS-immobilized silver nanoparticles (CNFS/Ag NPs).Materials and methodsCNFSs were immersed in suspensions of Ag NPs (5.17 ± 1.9 nm in diameter; mean ± SD) for 30 min at room temperature to produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 33 publications
2
39
0
1
Order By: Relevance
“…In our previous studies, Ag NPs were stably adsorbed onto chitin/chitosan powders [6,28] and sheets [29] with nanoscale fiber-like surface structures. In those applications, Ag NPs/chitin/chitosan composites showed enhanced stability of Ag NPs and exhibited strong antimicrobial (antiviral, bactericidal, and antifungal) activities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous studies, Ag NPs were stably adsorbed onto chitin/chitosan powders [6,28] and sheets [29] with nanoscale fiber-like surface structures. In those applications, Ag NPs/chitin/chitosan composites showed enhanced stability of Ag NPs and exhibited strong antimicrobial (antiviral, bactericidal, and antifungal) activities.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, chitin-nanofiber sheets (CNFS) were used to adsorb and to stabilize Ag NPs, remove the caramel generated during autoclaving, and prevent aggregation and precipitation of Ag NPs. Ag NPs were homogenously dispersed and stably adsorbed onto CNFS with nanoscale fiber-like surface structures [29]. Subsequent studies showed that the bactericidal, antifungal, and antiviral activities of Ag NPs/CNFS increased with Ag NP adsorption, indicating potential applications of CNFS as novel stabilizers and carriers for Ag NPs [27,29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal oxide particles have many functions, such as optical properties, 23,24 catalytic activities, 25 antimicrobial activities, 26 and the absorption properties. 27 Therefore, the metal oxide particles have been used as engineering materials, catalysts, absorbents, and biomedical materials.…”
Section: Introductionmentioning
confidence: 99%